Inferior alveolar nerve block anesthesia in children: The effect of ibuprofen and phentolamine mesylate on pain perception - Ullal Anand Nayak; Saravanan Ramasamy; Kavitha Odathurai Marusamy; Prathibha Anand Nayak; Amit Vanka (Wolters Kluwer Medknow Publications, 2024)
Context: For successfully managing pediatric dental patients, local anesthesia is essential to eliminate pain during or after the operative period. An early recovery from soft-tissue anesthesia after an inferior alveolar nerve block (IANB) should benefit a young child patient by avoiding the risk of inadvertently biting the soft tissues. Aims: Hence, the purpose of the study was to (1) evaluate and compare the efficacy of pre- and postoperative ibuprofen on pain perception in children who undergo IANB anesthesia with or without the use of PM and (2) evaluate the average time required for reversal of anesthesia symptoms using phentolamine mesylate. Methods: The present study was a randomized, clinical trial performed among 60 children between 6 and 8 years of age using a convenient sampling method. The children were randomly assigned into four equal groups of 15 each using the computer-generated randomization sequence. IANB anesthesia was performed using 2% lignocaine with 1:100,000 epinephrine, and a mandibular primary molar pulpotomy was performed on each group. Group 1: the ibuprofen tablet was taken 1 h before the onset of the procedure. Group 2: ibuprofen tablet 30 min after the pulpotomy procedure. Group 3: the ibuprofen tablet was taken 1 h before the onset of the procedure, and the Phentolamine mesylate (PM) injection was administered. Group 4: immediately after the pulpotomy, the PM injection was administered, and an ibuprofen tablet was taken 30 min after the pulpotomy procedure. All children were assessed for the duration of soft-tissue anesthesia, their behavior scores and pain rating, as well as the incidence of postoperative self-inflicted injuries. Statistical Analysis Used: A one-way ANOVA was used to compare the average time needed for the reversal of anesthetic symptoms between groups. The effects of phentolamine, local anesthetics, and ibuprofen on the child's behavior and pain scores were compared using the Student's t-test. For the study, P < 0.05 was accepted as statistically significant. Results: The time needed for the full reversal of anesthetic symptoms to manifest on the tongue and lip was substantially reduced by the injection of phentolamine (P < 0.001). The use of phentolamine for reversal or the intake of ibuprofen pre- or postoperatively did not exhibit any significant variation in the behavior, pain experience, or incidence of self-inflicted injuries in the child. Conclusion: It is evident that although phentolamine injections shorten the duration of anesthesia, the adjunctive use of pre- or postoperative ibuprofen did not significantly alter pain scores.